Optimization of amplitude-frequency characteristic of broadband voltage divider intended for measurement of power quality parameters - Brzhezitsky, Volodymyr; Trotsenko, Yevgeniy; Haran, Yaroslav (Technology audit and production reserves, 2020)
The object of research is the circuit diagram of a broadband capacitive-resistive voltage divider with a series-parallel connection of its resistive and capacitive components. For many years, the use of voltage dividers was limited to measuring various voltages in high-voltage laboratories. However, voltage dividers, compared to voltage transformers, are characterized by a wider bandwidth, therefore they began to be considered as one of the main means of measuring voltages in high-voltage electric networks. One of the catalysts for the implementation of this solution may be the intensive development of the Smart Grid concept, which requires new, more advanced means of monitoring the quality of electric power. Therefore, experimental and theoretical studies aimed at reducing the error of broadband voltage dividers are important. The task of optimally adjusting the low voltage arm of the voltage divider is solved by using linear programming elements to study the systematic error function. This article presents the results of the study of adjusting the amplitude-frequency characteristics of the voltage divider, which are aimed at reducing its error. For this purpose, a parameter for optimizing the capacitance value of low-voltage arm at which the absolute value of the positive and negative maximum of the systematic error of the capacitive-resistive voltage divider will be the same was found. The calculations are performed for different values of the division ratio of the voltage divider. The resulting data sets are generalized in the form of three-dimensional graphs. The work contributes to the further development of the theory of high-voltage voltage dividers. As a result of the studies, the possibility of optimizing the amplitude-frequency characteristics of a broadband capacitive-resistive voltage divider by varying the capacitance value of its low-voltage arm is shown. The studies are relevant due to the fact that this category of high-voltage scale transducers has the potential to become mandatory for determining the quality of electric energy directly in high-voltage networks.